2016
DOI: 10.1021/acs.bioconjchem.6b00205
|View full text |Cite
|
Sign up to set email alerts
|

RGD-Targeted Liposome Binding and Uptake on Breast Cancer Cells Is Dependent on Elastin Linker Secondary Structure

Abstract: The linker between the targeting moiety and the nanoparticle is often overlooked when engineering targeted drug delivery vehicles. We hypothesized that pH-triggered conformational changes of an elastin-like peptide (ELP) linker, with repeating VPGVG sequences, could alter the binding affinity of the well-established targeting moiety arginine-glycine-aspartic acid (RGD), which is known to enhance the delivery of nanoparticles to tumor cells via integrin overexpression. The pH change from blood (pH 7.4) to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Sonication is maybe the most widely applied method for the preparation of liposomes and nanoliposomes. Sonication is a simple technique for dropping the size of liposomes and production of nanoliposomes (Veneti et al 2016, Eatemadi et al 2016). There are some disadvantages for this method such as very low internal volume/encapsulation efficiency, removal of large molecules and metal pollution from probe tip (Yu and Tang 2016).…”
Section: Sonicationmentioning
confidence: 99%
“…Sonication is maybe the most widely applied method for the preparation of liposomes and nanoliposomes. Sonication is a simple technique for dropping the size of liposomes and production of nanoliposomes (Veneti et al 2016, Eatemadi et al 2016). There are some disadvantages for this method such as very low internal volume/encapsulation efficiency, removal of large molecules and metal pollution from probe tip (Yu and Tang 2016).…”
Section: Sonicationmentioning
confidence: 99%
“…Since the ELP linker showed conformational change in an acidic tumor microenvironment, the liposome-modified RGD-ELP linker significantly recognized both MDA-MB-231 and HCC1806 breast cancer cells. 109) These findings indicate that spacer peptides contribute to the efficacy of peptide-ligand-mediated active targeting.…”
Section: Perspectivesmentioning
confidence: 92%
“…Compared with PEGylated liposomes using PEG spacers, the combination of liposomal PEG350 and EG12 spacer dramatically improved its accumulation by 9-and 100-fold in breast cancer and multiple myeloma cells, respectively. 108) As another linker, Veneti et al 109) reported an elastin-like peptide (ELP) linker for RGD-targeted liposomes. Since the ELP linker showed conformational change in an acidic tumor microenvironment, the liposome-modified RGD-ELP linker significantly recognized both MDA-MB-231 and HCC1806 breast cancer cells.…”
Section: Perspectivesmentioning
confidence: 99%
“…[182][183][184][185][186][187][188][189][190][191] Recently, thermoresponsive ELP-liposomes have gained attention for their ability to allow release of drugs when exposed to mild hyperthermia. [163][164][165][166][167]192] Due to the hydrophobicity of the lipid bilayer, ELPs in ELP-liposomes have been modified with either a reactive group to decorate the hydrophilic head group of the liposomes that is exposed to aqueous solution, [163,164] or a lipid moiety to anchor the ELPs into the lipid bilayer. [165][166][167] The T t of the ELPs has been tuned to ≈40°C to match the temperature suitable for mild clinical hyperthermia of tissues.…”
Section: Elp-liposomesmentioning
confidence: 99%